PENENGGELAMAN KAPAL TERKAIT TINDAK PIDANA ILLEGAL FISHING SEBELUM ADANYA PUTUSAN PENGADILAN YANG BERKEKUATAN HUKUM TETAP - Banan Prasetya (JURNAL AKTA YUDISIA, 2020)
ABSTRACTThis research will be reviewed by the legal facts of the act of sinking illegal fishing vessels conducted by law enforcement officers or fisheries investigators in the Indonesian Fisheries Waters. The sinking of ships was carried out given the increasingly widespread theft of fish by foreign ships. An interesting legal issue to explore is about the sinking of illegal fishing vessels in a review of Indonesia's legal perspective. The purpose of this study is to analyse the sinking of ships related to the crime of illegal fishing before a court decision has permanent legal force, whether it is following applicable law. The next objective is to analyse the legal consequences of the ship sinking in the practice of enforcing illegal fishing criminal acts before a court decision has permanent legal force. This research is legal research with normative legal research type so that the analysis method used is a qualitative study that is built based on legal arguments to answer the problematic issues of this research law. The results showed that the act of sinking illegal fishing vessels in Indonesian fisheries waters by law enforcement officers or Indonesian fisheries investigators, normatively dogmatically, was following the provisions of Indonesian national law, which had been informed in Article 69 Paragraph 4 of Law Number 45 the Year 2009 regarding Fisheries, has also been by the provisions of international law, as regulated in Article 73 of UNCLOS 1982. Furthermore, the legal consequences of the sinking of illegal fishing vessels before the existence of a court decision have permanent legal force, normatively, has juridical implications on three things, namely: First, after the sinking of illegal fishing vessels became the basis for law enforcement officers or fisheries investigators to conduct further investigations within the formal criminal law enforcement framework; Second, the sinking of the ship has a legal effect on the status of the ship that sunk into status as evidence of the proceeds of crime or criminal acts that can be confiscated; Third, the sinking of the illegal fishing vessel has legal implications on the offender who can be subject to the status of a suspect and can even be raised to the status of a defendant of an illegal fishing crime. The author recommends that the Indonesian government through the foreign ministry should make diplomatic efforts to the international community to urge the United Nations to make illegal fishing a transnational crime. The procedure of permanent sinking of illegal fishing vessels, should not only be limited to the regulations of the Director-General of Fisheries but by the Indonesian government in the form of special legislation. Kata Kunci: Penenggelaman Kapal, Illegal Fishing, dan Penegakan Hukum